Lean ammonia-fueled engine operation enabled by hydrogen-assisted turbulent jet ignition - Reggeti, Shawn A.; Northrop, William F. (Frontiers in Mechanical Engineering, 2024)
Anhydrous ammonia (NH 3 ) use in internal combustion engines represents a zero-carbon energy solution that is fully sustainable if NH 3 is generated renewably. An active hydrogen-fueled pre-chamber to induce turbulent jet ignition (TJI) is investigated in this work as a means to enhance ignition energy and turbulent flame speed in an NH 3 fueled engine. The strength of the turbulent jets, and thus their effectiveness in igniting the main-chamber and enhancing combustion, is highly dependent on pre-chamber equivalence ratio and hydrogen fraction. Local pre-chamber mixtures are varied in the present study by investigating a range of pre-mixed intake NH 3 -air equivalence ratios (ϕ=0.5-1) under a consistent hydrogen direct injection strategy in the pre-chamber. Additionally, given the knock-resistance of NH 3 , multiple compression ratios were studied to investigate the impact on efficiency, emissions, and the combustion process.Results show a clear trade-off where leaner intake equivalence ratios enhance the reactivity of the pre-chamber (greater local hydrogen fraction and closer to stoichiometry) but reduce the reactivity of the main-chamber (lean and slow flame speed). Spark timing optimizes the trade-off under a fixed injection strategy; advancing spark provides more time for combustion to occur in the main-chamber but inhibits pre-chamber reactivity for a less energetic ignition of the main chamber. Optimal indicated thermal efficiency and minimum unburned NH 3 and N 2 O emissions occur around 0.7-0.8 equivalence ratio for all compression ratios. Conversely, NO x is highest at these equivalence ratios but could theoretically be eliminated using selective catalytic reduction aftertreatment using the NH 3 present in the exhaust.